Sustainable Food Production Systems and Resilient Agricultural Practices in Sri Lanka - Chandramohan, D.; Pakeerathan, K. (Springer Nature, 2026)
This chapter explores the vital role of food systems and resilient agricultural practices in Sri Lanka, addressing challenges such as climate change, environmental degradation, and socio-economic issues. It emphasizes that without robust agriculture, expectations for food security and rural economic growth are unrealistic. The chapter presents key strategies, including sustainable agricultural expansion and climate-smart practices, which enhance productivity while protecting ecological systems. It emphasizes sustainable models like organic farming and agroforestry that improve productivity without harming biodiversity. To increase resilience against climate impacts, the chapter advocates for introducing climate-tolerant crop varieties, better water management through a dedicated water authority, and enhanced disaster risk reduction strategies. The importance of national policies, government initiatives, and research center involvement, along with the need for strong public–private partnerships and the role of international organizations are discussed. The sustainability of Sri Lanka’s agriculture and allied sectors depends on responsive strategies that tackle evolving climate and resource challenges, ensuring food security and supporting the livelihoods of farming communities.
Keywords: Climate resilience; Climate resilience; Sustainable agriculture; SDG; Sri Lanka